Analysis of pigment, physical and chemical characteristics of bottom sediments in lakes Naroch and Myastro - Smolskaya, Olʼga S.; Zhukava, Hanna A.; Lyulya, Anastasia S. (Experimental Biology and Biotechnology, 2019)
In the samples of the surface layer the bottom sediments of the Naroch and Mуastro lakes, collected in the summer of 2016 and 2017, the main physical and chemical parameters (density, wetnessand organic matter content), as well as the content of chlorophyll and its decay products were studied. Pigment indices that reflect the general conditionof the producers in the ecosystem, primarily phytoplankton: Е450 /Е480, Е480 /Е664, Е430 /Е664, Е480 /Е665, Е480 /1,7Е665к, Е430 /Е412 were calculated. The auxiliary pigment indexes suggested for controlling the purity of the extract and the clarity of the prescribed spectrum: Е664 /Е720, Е430 /Е720, Е412 /Е720, Е530 /Е720, Е430 /Е530, Е664 /Е530 и Е412 /Е664; can be used as quality criteria of the tested sample and its suitability for the calculation of pigment indices characterizing the state of producers in an ecosystem.